Alopecia areata incognita in Cronkhite–Canada syndrome. (24th May 2017) - Ong, S.; Rodriguez‐Garcia, C.; Grabczynska, S.; Carton, J.; Osborn, M.; Walters, J.; Kubba, F.; Stefanato, C.M.
Summary: Cronkhite–Canada syndrome is an acquired inflammatory polyposis syndrome in which alopecia, onychomadesis and hyperpigmentation occur concurrently with gastrointestinal symptoms. The pathophysiology of alopecia in Cronkhite–Canada syndrome has not been definitively elucidated. We present evidence for alopecia areata incognita as a possible mechanism of hair loss. Abstract : What's already known about this topic? The aetiology of Cronkhite–Canada syndrome and the mechanism of hair loss in this syndrome are not known. What does this study add? We present a case of Cronkhite–Canada syndrome and propose alopecia areata incognita as a possible pathological mechanism of hair loss. Linked Comment:  Stefanaki and Stratigos. Br J Dermatol 2017;177 :348–349